Cardiac reparative therapy with adipose graft transposition procedure reduces slow conduction areas in a chronic myocardial infarction swine model. (24th May 2021) - Adelino Recasens, R; Galvez-Monton, C; Martinez-Falguera, D; Curiel, C; Marsal, R; Teis, A; Rodriguez-Leor, O; Fadeuilhe, E; Sarrias, A; Bazan, V; Villuendas, R; Aranyo, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Insituto de Salud Carlos III BACKGROUND: Cardiac regenerative therapy is a promising treatment for patients with ischemic heart disease, but there are some concerns on the potential increased risk of arrhythmic events following specific cell therapies. Adipose graft transposition procedure (AGTP) is a cardiac reparative therapy consisting in transposing a vascularized adipose flap from the autologous pericardium and placing it over the epicardial scar area and has demonstrated to reduce infarct size and improve the left ventricular ejection fraction in preclinical and human studies. Specific electrophysiological properties of the scar, (i.e. slow conduction velocity (CV)) have been identified as key features of ventricular tachycardia (VT) isthmuses. PURPOSE: To assess the effect of the AGTP on VT inducibility and the electrophysiological properties of the post-MI scar with ultra-high density (UHD) mapping. METHODS: A left circumflex artery (first marginal branch) MI was induced in 10 Landrace X Large White pigs by delivering 1-3 coils. Two weeks post-MI, all subjects underwent baseline left ventricular endocardial UHD mapping during right ventricular pacing with 64-electrode basket mapping catheter, as well as electrophysiological study (EPS) to test for VT inducibility.  Following the mapping, subjects were allocated 1:1 to AGTP or sham group. UHD mapping and EPS were repeated 30 days post-treatment (6 weeks after MI). Voltage and activation maps were analyzed off-line with self-customized Paraview-based software. Voltage cut-offs of 1.5 and 0.5mV (bipolar) defined normal tissue, border zone (BZ) and dense scar, respectively, and 6.7mV for unipolar. Conduction velocity (CV) was determined for every pair of contiguous points and areas of similar CV were quantified for every 0.2m/s steps (for up to 4 m/s). RESULTS: There were no differences between groups with regard of dense scar, BZ an low unipolar voltage areas. The AGTP group had a significant reduction of the size of slow CV (<0.2 m/s) areas, compared to the sham group in whom it increased (-4.1 ± 1.7 vs. +2.4 ± 1.6 mm2, p = 0.028)(Figure). There were no differences in the size of other ranges of CV. EPS did not induce VT in any subject at baseline, and only in 1 of the sham group at the follow-up EPS. CONCLUSIONS: Cardiac reparative therapy with AGTP of post-MI scar reduced the size of slow conduction areas and could provide a protective effect against arrhythmic events in ischemic heart disease.